2016
DOI: 10.1038/ng.3489
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neutral tumor evolution across cancer types

Abstract: Despite extraordinary efforts to profile cancer genomes, interpreting the vast amount of genomic data in the light of cancer evolution remains challenging. Here we demonstrate that neutral tumor evolution results in a power-law distribution of the mutant allele frequencies reported by next-generation sequencing of tumor bulk samples. We find that the neutral power-law fits with high precision 323 of 904 cancers from 14 types, selected from different cohorts. In malignancies identified as neutral, all clonal se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
773
12
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 581 publications
(861 citation statements)
references
References 49 publications
55
773
12
5
Order By: Relevance
“…Specifically, while evidence for selection of driver events in cancer development, as well as the selection pressures imposed by therapy, are undisputed, following a 'big-bang' of diversity early in tumor evolution, ITH development can follow the laws of neutral growth (Sottoriva et al, 2015). In support of this, Williams and colleagues noted that, for a subset of tumors, the relationship between the number of subclonal mutations and their relative abundance was consistent with a neutral growth pattern rather than subclonal expansions (Williams et al, 2016). Likewise, in an extensively sampled colorectal cancer the degree of heterogeneity appeared more consistent with neutral growth (Ling et al, 2015), and lineage-tracing studies in mice have suggested ITH may emerge from a stem-cell hierarchy of cancer cells evolving under neutral evolution (Driessens et al, 2012).…”
Section: Processes Of Cancer Genome Evolution and Evolutionary Debatesmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, while evidence for selection of driver events in cancer development, as well as the selection pressures imposed by therapy, are undisputed, following a 'big-bang' of diversity early in tumor evolution, ITH development can follow the laws of neutral growth (Sottoriva et al, 2015). In support of this, Williams and colleagues noted that, for a subset of tumors, the relationship between the number of subclonal mutations and their relative abundance was consistent with a neutral growth pattern rather than subclonal expansions (Williams et al, 2016). Likewise, in an extensively sampled colorectal cancer the degree of heterogeneity appeared more consistent with neutral growth (Ling et al, 2015), and lineage-tracing studies in mice have suggested ITH may emerge from a stem-cell hierarchy of cancer cells evolving under neutral evolution (Driessens et al, 2012).…”
Section: Processes Of Cancer Genome Evolution and Evolutionary Debatesmentioning
confidence: 97%
“…As such, the extent to which positive selection can account for the degree of ITH in tumors has been called into question (Ling et al, 2015;Williams et al, 2016). Specifically, while evidence for selection of driver events in cancer development, as well as the selection pressures imposed by therapy, are undisputed, following a 'big-bang' of diversity early in tumor evolution, ITH development can follow the laws of neutral growth (Sottoriva et al, 2015).…”
Section: Processes Of Cancer Genome Evolution and Evolutionary Debatesmentioning
confidence: 99%
“…On the contrary, progressor alterations accumulated in few driver genes, and the passenger mutations fostered neutral evolution. According to the distribution of variant allele frequency (VAF), neutral evolution was observed in 30% of all malignancies 41. Our previous whole‐exome sequencing (WES) study by MRA showed neutral evolution in advanced CRC cases, which was validated by computational simulation analysis.…”
Section: General Components Of Ithmentioning
confidence: 70%
“…These mutations are the result of replication errors during cell division and their frequency distribution is a consequence of each cancer's evolutionary history. In our latest work 1 we utilized the distribution of mutant allele frequencies of tumors to infer how individual cancers grew.…”
Section: Introductionmentioning
confidence: 99%
“…Equation [1] has been described previously in the population genetics literature, 2,3 but has not to our knowledge been applied to cancer genomes. We tested the prediction of our model on next-generation sequencing data from 904 tumors of many different types.…”
Section: Introductionmentioning
confidence: 99%